THE RISKS OF SUNLIGHTING CLASSROOMS. An appraisal method to assess the severity of discomfort due to sunlight penetration in classrooms. Site of study: Primary school classrooms in Constantine (ALGERIA) (Sciences & Technology. A, exactes sciences, 2001)
The westerly orientations for a large number of primary school classrooms in Constantine involved a serious environmental problem provoked by uncontrolled sunlight. Under such circumstances the schoolchildren had no choice than keep sitting under incident sunlight while performing their various school tasks.  Evidence of the severity of discomfort experienced by those pupils was investigated using observational methods. The results allowed to reach substantial conclusions about the risks of sunlighting classrooms.